Member of the External Evaluation Committee for the Department of Electronics of the Technological Educational Institution of Central Greece - Tsapatsoulis, Nicolas (My University, 2026)
Member of the External Evaluation Committee for the Department of Electronics of the Technological Educational Institution of Central Greece